Computation of the scintillation index and BER of super Lorentz Gaussian laser beam in a slant propagation at atmospheric turbulence - Hussein Thary Khamees; Sameer Algburi; Hussein E. Kotb (Ain Shams Engineering Journal)
Modern free-space communication systems require a comprehensive analysis of how atmospheric turbulence impacts the scintillation index and the bit-error rate (BER). In this paper, we model the laser light with Super Lorentz Gaussian Beams (SLGBs) intensity distribution slant propagation between the transmitter and receiver planes. The Huygens-Fresnel Method is employed to compute the received field due to its effectiveness in accurately modeling atmospheric turbulence. A 50° zenith angle results in the lowest on-axis scintillation index. The receiver plane aperture area size plays a crucial role in this analysis. For an aperture area that covers 25 % of the receiver plane, the SLGB00 almost exhibits the lowest scintillation index. The SLGB22 scintillation index approaches SLGB00 at a laser wavelength of 1.55 µm. We reduced the receiver aperture area to 1.4 × 10−3% and computed the on-axis scintillation index and the BER for both SLGB00 and SLGB22. SLGB22 shows the lowest on-axis scintillation index and BER.